KOMITMEN DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Slamet Aji Winoto; Sidik Priadana; Dewi Yuliati Indah (Jurnal Riset Bisnis dan Manajemen, 2020)
Organizational Citizenship Behavior (OCB) is an individual contribution that exceeds the demands of roles in the workplace. This study was conducted to determine the effect of organizational commitment and organizational culture on OCB on employees of PT Taspen (Persero) KCU Bandung. This study used saturated samples were 41 respondents. Method used were descriptive and verificative, using multiple linear regression, multiple correlation, and coefficient of determination analysis. The results showed that simultaneously organizational commitment and organizational culture influence on OCB of 81.3%. Partially, it is known that the influence of organizational commitment on OCB is 67.3%, while organizational culture has an influence of 14.0%.